2002
DOI: 10.1099/00221287-148-6-1881
|View full text |Cite
|
Sign up to set email alerts
|

Location of functional groups in mycobacterial meromycolate chains; the recognition of new structural principles in mycolic acids

Abstract: Mycobacterial α-, methoxy-and keto-mycolic acid methyl esters were separated by argentation chromatography into mycolates with no double bond, with one trans double bond or with one cis double bond. Meromycolic acids were prepared from each methyl mycolate fraction by pyrolysis, followed by silver oxide oxidation, and analysed by high-energy collision-induced dissociation/fast atom bombardment MS to reveal the exact locations of the functional groups within the meromycolate chain. The locations of cis and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
130
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(133 citation statements)
references
References 36 publications
3
130
0
Order By: Relevance
“…This mass corresponds to a dicyclopropanated ␣-mycolate of 79 total carbons with a 24-carbon ␣ branch as pictured in Fig. 1 and as reported previously for other strains of Mtb (24,25). In addition, peaks at 1123 and 1179 reflect smaller and longer chain length variants by two methylene units.…”
Section: Construction Of An Mtb Mmaa2mentioning
confidence: 57%
“…This mass corresponds to a dicyclopropanated ␣-mycolate of 79 total carbons with a 24-carbon ␣ branch as pictured in Fig. 1 and as reported previously for other strains of Mtb (24,25). In addition, peaks at 1123 and 1179 reflect smaller and longer chain length variants by two methylene units.…”
Section: Construction Of An Mtb Mmaa2mentioning
confidence: 57%
“…Thus changes in the proportion of methoxy-and keto-MA had already been reported during cultivation of Mycobacterium microti [26]. In a second landmark paper, Watanabe et al identified and collated the positions of the functional groups in the meromycolate fragments of the MA, revealing the full complexity of the mixtures present and again showing considerable difference between H37Ra and other M.tuberculosis strains [25]. Table 2 lists the major components of the series of homologues identified for M.tuberculosis that contain two functionalities X and Y in the chain.…”
Section: Structural Properties Of Mycolic Acids Of Mycobacterium Specmentioning
confidence: 81%
“…The detailed patterns of the mycolic acid components of a number of strains of M. tuberculosis and some other mycobacteria have been elegantly collected through the work of Watanabe et al [24,25]. The total mixture of methyl esters was analysed first by 1 H NMR spectroscopy, then separated into α-, methoxy and ketomycolates.…”
Section: Structural Properties Of Mycolic Acids Of Mycobacterium Specmentioning
confidence: 99%
“…α-Mycolates: its meromycolate chain contains two ciscyclopropanes; Methoxymycolates: its meromycolate chain contains an a-methyl methyl-ether moiety in the distal position and a ciscyclopropane or an α-methyl trans-cyclopropane in the proximal position; Ketomycolates: its meromycolate chain contains an α-methyl ketone moiety in the distal position and proximal functionalities as in the methoxy series. It should be pointed out that, more recently, unsaturations have been detected in the meromycolate chain of M. tuberculosis (Watanabe et al 2002), which are not shown here. (Kremer et al 2003).…”
Section: Biosynthesis Of Mycolic Acids (Fas-ii System)mentioning
confidence: 93%